BBC Micro:bit in practice : a hands-on guide for building creative real-life projects with MicroPython and BBC Micro:bit /: a hands-on guide for building creative real-life projects with MicroPython and BBC Micro:bit. (2023) - Pajankar, Ashwin; (Robotics engineer), Sharma, Abhishek; Saini, Sandeep
No abstract available